A practical approach to measuring the acoustic diversity by community ecology methods. Issue 5 (11th February 2021) - Zsebők, Sándor; Schmera, Dénes; Laczi, Miklós; Nagy, Gergely; Vaskuti, Éva; Török, János; Zsolt Garamszegi, László
Abstract: The study of the diversity of animal signals on within‐ and among‐species levels is the key to uncover mechanisms that shape the evolution of communication systems. However, the methods used to quantify acoustic diversity (like repertoire size) lack to grasp several aspects of acoustic diversity. Here, we propose a new framework for the study of animal communication, in which we decompose the acoustic diversity with the methodological toolbox from community ecology. We explore how different diversity estimates reflecting different aspects of acoustic diversity can be applied to characterise the complexity of acoustic signals. We propose that this approach can be used in a wide range of animal taxa to derive further insights about the function and evolution of communication systems besides the traditional methods. To illustrate the use of our approach in a case study, we used the song of the collared flycatcher Ficedula albicollis as model system. Based on three frequency and time variables, we calculated three functional diversity indices (FRic, FEve and FDiv) to characterise the distribution of song elements (syllables) in the acoustic parameter space. We aimed to uncover the interrelations of diversity indices, reveal the degree of among‐individual consistency and investigate their relationships with certain aspects of individual quality (body condition, age and arrival date). We found that the diversity indices were largely independent of each other and showed different consistency patterns that were time‐scale dependent, indicating different signalling potential of individual‐specific attributes. We also found that FEve strongly related to the age of males. Our case study showed that decomposing the diversity into different components can reveal additional biologically meaningful aspects of birdsong.